PERANG OBOR: EKSPLORASI ASAL-USUL, RANGKAIAN UPACARA, DAN PERSPEKTIF MASYARAKAT DESA TEGALSAMBI - Melya Milviana (Yayasan Pendidikan Literasi Borneo, 2025)
Perang Obor is an annual tradition in Tegalsambi Village, Tahunan District, Jepara Regency, that holds significant historical, cultural, and local wisdom values. The tradition originates from an oral tale about a conflict between Kiai Babadan and Ki Gemblong, which culminated in the use of torches as weapons, believed to heal livestock and serve as a form of earth-offering ritual. This study aims to explore the origins, ceremonial sequence, and community perspectives of Perang Obor through an ethnohistorical approach combining historical sources, oral narratives, and field observations. The three-day procession begins with ancestral thanksgiving rituals, buffalo sacrifice, wayang kulit performances, communal feasts, and concludes with a symbolic and controlled torch battle. The community perceives it as an expression of gratitude, a means to ward off misfortune, a tribute to ancestors, and a reinforcement of solidarity. Furthermore, the tradition serves as both a cultural identity and a tourism attraction. In conclusion, Perang Obor functions as a cultural heritage that integrates spiritual, social, and economic values while strengthening community unity amid modernization.